Integrated assessment of competitive-strategy selection with an analytical network process - Lee, Yun-Huei; Lee, Yun-Huan (Journal of Business Economics and Management, 2012)
The present study explores efforts to identify the most appropriate competitive strategy relative to multinational biotech pharmaceutical enterprises’ strategy selection. The research uses the analytic network process (ANP) technique combining both qualitative and quantitative information to construct a hierarchical model involving interactions among various criteria for competitive-strategy selection. The most important finding shows that the most suitable competitive strategy for multinational enterprises (MNEs) is differentiation strategy. The weighted calculations reveal important criteria: an external environment analysis reveals that the three most important criteria affecting FDI competitive strategy are population size, per capita income, and healthcare and medical insurance systems; a core competency analysis reveals that the three most important criteria affecting competitive-strategy selection of FDI to China are capability in collaborating with local partners, possession of high-quality research personnel with R&D capability, and possession of a strong brand.